2018
DOI: 10.1111/ejh.13155
|View full text |Cite
|
Sign up to set email alerts
|

Needs for information and reasons for (non)adherence in chronic myeloid leukaemia: Be aware of social activities disturbing daily routines

Abstract: Nonadherence to CML medication does not cause concern in all patients and is not discussed pro-actively. HCP have a clear role in supporting medication adherence in CML and must be aware that social activities disturbing daily routines contribute to nonadherence. HCP should discuss (non)adherence in a direct manner, motivate patients to play an active role in managing their medication and timely provide extensive and understandable information on all aspects of CML.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
34
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(39 citation statements)
references
References 48 publications
4
34
0
1
Order By: Relevance
“…Optimal adherence to TKI treatment is paramount to achieving an optimal molecular response, while its depth is related to treatment duration [15][16][17]31]. Despite these requirements, awareness of the possibility of successful TKI treatment discontinuation and knowledge that in the event of relapse treatment can be successfully resumed, will encourage patients who have been treated for a long time to interrupt TKI treatment for shorter or longer periods [8,[32][33][34][35]. HCPs counseling patients on longterm TKI treatment must be aware of this paradox which also urgently requires more clarity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Optimal adherence to TKI treatment is paramount to achieving an optimal molecular response, while its depth is related to treatment duration [15][16][17]31]. Despite these requirements, awareness of the possibility of successful TKI treatment discontinuation and knowledge that in the event of relapse treatment can be successfully resumed, will encourage patients who have been treated for a long time to interrupt TKI treatment for shorter or longer periods [8,[32][33][34][35]. HCPs counseling patients on longterm TKI treatment must be aware of this paradox which also urgently requires more clarity.…”
Section: Discussionmentioning
confidence: 99%
“…Especially in patients who are not yet receiving old age benefits, particularly those between 55 and 65-70 years of age, the lack of income from work can be a burden. Indeed, side effects of TKI treatment, fatigue in particular, as well as stress and mental issues are known to impact on patient activities of daily living and prevent them to work [8,32]. It has also been found that patients who discontinued treatment felt a great sense of relief and freedom [37].…”
Section: Discussionmentioning
confidence: 99%
“…Common informational needs include those related to prognosis, how to care for someone with cancer, and the benefits and toxicities of treatment [ 2 , 8 - 14 ]. Unmet information needs are associated with decreased treatment adherence [ 15 , 16 ], increased health care costs [ 17 - 19 ], anxiety [ 20 , 21 ], and depression [ 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…For instance, although existing theoretical frameworks employed in the HISB cancer context [ 29 , 47 - 49 ] describe a cost-benefit relationship in terms of whether an individual will search for additional information, they do not provide guidance in terms of how to structure interventions for those affected by cancer to minimize the cost and maximize the benefit of information seeking. A theoretical framework that addresses this gap in the literature is thought to be valuable for developing interventions that address the informational needs of those living with cancer [ 1 , 4 , 11 , 12 , 14 , 15 , 35 , 38 , 48 ]. Such a framework would be capable of informing the development of interventions that support individuals in planning their lives around the short- and long-term consequences of cancer, including the receipt of treatment and altered life expectancy [ 22 , 50 ].…”
Section: Introductionmentioning
confidence: 99%
“…Due to apparently successful treatment, patients increasingly participate in social and occupational activities. However, this often interferes with their daily routines which makes patients more easily to forget or skip a dose [39,59,60,17]. On the other hand, intentional nonadherence is mostly due to perceptual barriers (i.e., beliefs) [61,62].…”
Section: Discussionmentioning
confidence: 99%